2011
DOI: 10.1002/jor.21515
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1α, ‐6, and ‐8 decrease Cdc42 activity resulting in loss of articular chondrocyte phenotype

Abstract: Small GTPase proteins mediate changes in cellular morphology and other cellular functions. The aim of this study was to examine signaling of the small GTPase Cdc42 by stimulating chondrocytes grown in monolayer with long-(96 h) or short-(2 and 30 min) term exposure to interleukin-1a (IL-1a), IL-6, or IL-8. Quantitative PCR was used to determine changes in collagen type IIB (COL2A1), aggrecan (AGG), and matrix metalloproteinase-13 (MMP-13) gene expression after prolonged cytokine exposure. Effects of short-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
2
24
1
1
Order By: Relevance
“…Exposure to Il6 recapitulates select effects of Notch in chondrocytes, and we tested whether Notch signaling regulates Il6 expression in chondrocyte-enriched cells from Rosa Notch mice infected with Ad-CMV-Cre to induce NICD or with control Ad-CMV-GFP 26,27,28,29 . Analysis of mRNA levels by qRT-PCR revealed that activation of Notch signaling induced a 7 fold increase in Il6 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to Il6 recapitulates select effects of Notch in chondrocytes, and we tested whether Notch signaling regulates Il6 expression in chondrocyte-enriched cells from Rosa Notch mice infected with Ad-CMV-Cre to induce NICD or with control Ad-CMV-GFP 26,27,28,29 . Analysis of mRNA levels by qRT-PCR revealed that activation of Notch signaling induced a 7 fold increase in Il6 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of chondrocytes to Il6 phenocopies selected effects of Notch signaling, and we asked whether Il6 mediates the effects of Notch on the expression of chondrocyte gene markers 27,28,29 . To investigate this possibility, chondrocyte-enriched cells from Rosa Notch mice were exposed to a neutralizing murine monoclonal IgG raised against Il6 or murine IgG, either in the context of Notch activation or under basal conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology of osteoarthritis is still unclear, but evidences have proved that pro-inflammatory cytokines produced from cartilage are released into synovial space and participate in the breakdown of articular cartilage, collagen fibers, ligaments and menisci [20,21]. Herein, ATDC5 cells were subjected to LPS to induce an in vitro model of cartilage damage.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin signaling has been shown to induce inflammatory cytokines [27,28] www.futuremedicine.com and in various cell types actin cytoskeletal remodeling has been shown to regulate cytokine secretion [29] and potentiate NF-kB signaling [30]. Although this has not been shown for chondrocytes, inflammatory cytokines have been shown to modulate the chondrocyte actin cytoskeleton [31], and, possibly, cytoskeletal remodeling in turn also affects cytokine production and/or secretion in this cell type. For cartilage regeneration using nonexpanded chondrocytes, the HyStem scaffold seemed most optimal.…”
Section: Polyactive™mentioning
confidence: 99%